The Purposes of Islamic Sharia Which Related to the Mandatory Provision - Dahman, Abdullah Ahmed Ahmed (Journal of Islamic Sciences, 2023)
This study aimed to explain the most important purposes of the Sharia related to the mandated rule, and the study used the inductive, analytical and deductive approach, to identify the objectives of the thesis. The main axes of the study dealt with the following topics: the definition of the purposes of Sharia, the mandated ruling and clarifying the purposes of Sharia related to the mandated ruling This study concluded a set of results, the most important of which are: 1- Objectives of the Sharia: It is the wisdom that the Lawgiver nurtured in legislation, as an endorsement of the servitude of God, the realization of human interests in both worlds, and ward off its evils. 2- The mandated ruling: It is the speech of God Almighty related to the actions of those charged with necessity, choice or situation. 3- The wise legislator has several purposes in enacting mandated rulings, including: establishing the servitude of God, realizing the human interests in the two worlds, building the earth, establishing the argument over creation, preserving lofty morals and values, establishing acquaintance, cooperation and integration among humanity.